Dietary supplements in health promotion - Wallace, Taylor C. (CRC Press, 2015)
The supplement market continues to grow annually with more than half of the population using these products for reasons spanning from health maintenance to disease prevention and/or treatment. Dietary Supplements in Health Promotion presents clear and concise evidence on how dietary supplements may contribute to maintaining health status. The book provides information on personalized nutrition, nutrient gaps, and postulated benefits of various mainstream dietary supplements such as multivitamins, probiotics, and flavonoids, among others.The book summarizes evidence to date so that health profe.
Keywords: Dietary supplements.; Health promotion.; elektronické knihy; electronic books